Information campaigns and local authorities - Mariekie Burger (Communicare)
The new constitution links the duties of local governments to development, implying that the financial dilemma of local authorities caused by the culture of non~payment for municipal services, should be seen in the light of the deve/opment~rientated situation in South Africa. As the failures of the authoritarian top-down development approach became evident, it is not '8 solution to remove the electricity cables of non-payers, neither is it a solution to modify behaviour only. The motivation behind a campaign aiming at correcting the situation should focus on the capacity building in the community, which is in line with participatory development and DSC thinking. This can only be· done in a participatory situation, where information is released about the operations of the local authority, and the community is educated about the functions and processes taking place in the local authority. In a workshop situation, the needs of the community should be prioritised, in order to address those needs. It is believed that by understanding the various functions and operations of the local authority, attitudes of the community will change towards the local authority, and that such change might lead to a change in the culture of non~payment.